Effect of parametric uncertainties on fracture behavior of cortical bone using XIGA. (15th June 2020) - Soni, Aakash; Kumar, Sachin; Kumar, Navin
Graphical abstract: Highlights: XIGA can be used to solve fracture problems involving complex geometries. XIGA provides smoother results for highly heterogeneous materials, even at coarser mesh. Parametric uncertainties have a significant effect on fracture behavior of cortical bone. The effect of porosity percentage and osteon modulus is pronounced. Abstract: Bone tissues are heterogeneous composites that consist of various microstructural constituents at different length scales. These microstructural constituents and their heterogeneous distribution significantly affect the fracture behavior of bones. Thus, the effect of parametric uncertainties on the fracture analysis of a cortical bone is presented in this study. A 2D model of the cortical bone is generated with the help of micro-CT image of a cortical bone and the fracture analysis is performed for the developed model with the help of an Extended Isogeometric Analysis (XIGA) using linear elastic fracture mechanics. The values of stress intensity factor are calculated with the help of interaction integral approach and the direction of crack propagation after each step is evaluated using the maximum principle stress criterion. The obtained results are compared with the finite element results using Abaqus software and found in good agreement. Further, uncertainties in the values of osteon Young's modulus, cement line thickness and porosity percentage are taken into consideration for stochastic analysis. The effect of variation in the values of input parameters on the stress intensity factor values and the crack path trajectories is illustrated, and observed that the variation in osteon Young's modulus and porosity percentage is more pronounced than the cement line thickness.